(3GdWgGQIs - (3eMeO Jbj GdMSjf GdMSjfj GdHZOGOjs
(3ChdgG (B:s
(3GdMeO ddg (B.. (3gPG cJGH GdWgGQI hajg ebOeI hebGUO hNGJeI ; CeG GdebOeI aajgG aUdGf ; GdChd aj GdeGA GdeWdb hajg eHGMK , GdChd aj GdLGQj hGdHMK ajg jbY aj ebGeGJ CMOgG ehVhYI hGdCbhi Cfg GdSGFd HGdaYd (B...s
(3BNQgG (B:s
... (3de jcf cd hGMO ajgG cGajG aj GKHGJ Pdc adG QjH hdG THgI aj EKHGJg eLehYgG GdChd Cf (B... (3hGdeOjfI GdefhQI hecI GdeTQaI hGdeJYGQa GdTGFY GdPGFY GdeYghO efg GdeSJOjQ hGdeOhQ Ohf GdeQHY aj ReGf GdEeGe GdeMOO dg (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis